Interactive Combustion in a Linear Array of 2D Laminar Isolated and Triple Burner Jets. (19th November 2012) - Tillman, S. T.; Kuchibhatla, S.; Annamalai, K.; Caton, J. A.; Ranjan, D.
Abstract : Many practical combustion systems such as residential gas burners contain dense groupings or clusters of jet flames with sufficiently small spacing between them, which causes flame interaction. The interaction effect, due in part to Oxygen deficiency in the interstitial space between the flames, causes the spreading of flames, which may merge together to form larger group flames. This interactive effect is studied analytically by revisiting the laminar isolated flame theory for 2D jets, for which similarity solutions are readily available in compressible form, and symmetrical interaction zones can be observed. Flame characteristics were studied by obtaining analytical expressions for flame specific parameters such as height and width, lift-off height and blow-off velocity, air entrainment and mixing layer growth. The theory for multiple interacting jets describes an approximate criterion for interburner spacing at which flame interaction and group flame formation are first observed. The analytical framework presented in this paper presented in this paper produced results which were compared with experimental measurements. The experimental apparatus allowed the interburner spacing to be varied from 7.87 mm to 50.8 mm, and measurements of flame height, width, lift-off height and group-flame formation under interactive modes. Images of the evolving flow field were taken and Schlieren images of the multiple 2D jets were also recorded using a digital camera.